Start-up of the completely autotrophic nitrogen removal over nitrite process with a submerged aerated biological filter and the effect of inorganic carbon on nitrogen removal and microbial activity. (April 2018) - Yue, Xiu; Yu, Guangping; Liu, Zhuhan; Lu, Yuqian; Li, Qianhua
Graphical abstract: Highlights: The CANON process with a SABF was rapidly initiated within 37 days. The phyla Proteobacteria and Planctomycetes represented the AOB and AnAOB. The dominant genus Candidatus Brocadia was the contributor to this CANON process. The IC was an important factor for the CANON process with a SABF. The IC/Nopt ratio was 1.2 with the ANR and TNR of 95.5% and 80.3%, respectively. Abstract: Good start-up and performance are essential for the completely autotrophic nitrogen removal over nitrite (CANON) process, and inorganic carbon (IC) is also important for this process. In this study, a lab-scale submerged aerated biological filter (SABF) was adopted for the CANON process. A 16S rRNA gene high-throughput sequencing analysis showed that the phyla Proteobacteria and Planctomycetes were the dominant microorganisms and that the genus Candidatus Brocadia functioned as the nitrogen remover. The effect of IC on the nitrogen removal was analyzed. The results showed that the optimum concentration ratio of IC to nitrogen (IC/N) was 1.2, which produced the highest average ammonium nitrogen removal rate (ANR) and total nitrogen removal rate (TNR) values of 95.5% and 80.3%, respectively. The average AOB and AnAOB activities were 2.45 mg·L −1 ·h −1 and 3.57 mg·L −1 ·h −1, respectively. This research could promote the nitrogen removal ability of the CANON process with a SABF in the future.